Tool wear and burr formation during drilling of aluminum alloy 7075 in dry and with cutting fluid - Dahnel, Aishah Najiah; Fauzi, Muhammad Haziq; A. Raof, Natasha; Mokhtar, Suhaily; Muhamad Khairussaleh, Nor Khairusshima (Elsevier, 2022)
Aluminum alloy 7075 (Al 7075) has been widely used in aerospace and automotive industries to replace heavier alloys. This is because of its superior properties of high specific strength, high corrosion resistance, good formability, recyclability and low fabrication cost. However, the ductility and heat generation during drilling Al 7075 often produces a burr at the entrance and exit of the workpiece surface. This research investigates the effect of cutting speeds and drilling conditions on the burr formation of Al 7075. Drilling was performed in dry and with conventional cutting fluid using 6.0 mm high speed steel drills with cutting speeds of 22, 44 and 66 m/min at a constant feed rate of 0.15 mm/rev. The use of cutting fluid in drilling Al 7075 caused lower tool wear by 42%, 38% and 30%, respectively, at 22, 44 and 66 m/min, compared to dry drilling. As for burr formation, drilling with cutting fluid on average resulted in 20% lower burr root width and 10% lower burr height than dry drilling for all cutting speeds. This study indicated that drilling Al 7075 using the cutting speed of 44 m/min with cutting fluid is beneficial as it resulted in the least tool wear and minimum burr formation.